Is Exercise Addiction in Adults a Meaningful Predictor of Their Attitudes Towards Nutrition? - Türkeli, Anıl (Progress in Nutrition, 2020)
The aim of this study is to determine whether exercise addiction in adults is a significant predictor of their attitudes towards nutrition by examining exercise addiction in adults and attitudes towards healthy nutrition. Relational Screening Model was used in the study. The study group consisted of 767 young people aged 18 and over. Exercise Addiction Scale (EAS) and Attitude Scale for Healthy Nutrition (ASHN) has been used in data collection. The relationship between exercise addiction and attitudes towards healthy nutrition has been examined using the Pearson Moments Multiplication Correlation. Multiple Linear Regression Analysis was conducted in order to examine the effect of exercise addiciton on adults’ attitudes towards healthy nutrition. The relevance level was found as 0.05. As a result of the research, it has been seen that exercise addiction in adults is a significant predictor of their attitudes towards healthy nutrition and it directly explains the 58% of points of attitudes towards healthy nutrition alone.